2021
DOI: 10.1016/j.cyto.2021.155523
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant cytokine expression in COVID-19 patients: Associations between cytokines and disease severity

Abstract: Cytokines play pleiotropic, antagonistic, and collaborative in viral disease. The high morbidity and mortality of coronavirus disease 2019 (COVID-19) make it a significant threat to global public health. Elucidating its pathogenesis is essential to finding effective therapy. A retrospective study was conducted on 71 patients hospitalized with COVID-19. Data on cytokines, T lymphocytes, and other clinical and laboratory characteristics were collected from patients with variable disease severity. The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…Previous reports analyzed the routine laboratory biomarkers at hospital admission for COVID-19, suggesting that the most severe forms of COVID-19 were associated with peripheral lymphocyte and neutrophil subsets alteration ( Al Balushi et al, 2021 , Cai et al, 2021b , Lu et al, 2021 , Reusch et al, 2021 , Wang et al, 2020 ). Similarly, a wide range of metabolic parameters and biomarkers of damage, inflammatory responses, and coagulation system activation have been associated with COVID-19 poor outcomes ( Charoenngam et al, 2021 , Heer et al, 2021 , Khamis et al, 2021 , Kitakata et al, 2021 , Lv et al, 2020 , Manocha et al, 2021 , Nurlu et al, 2021 , Tang et al, 2021 )…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports analyzed the routine laboratory biomarkers at hospital admission for COVID-19, suggesting that the most severe forms of COVID-19 were associated with peripheral lymphocyte and neutrophil subsets alteration ( Al Balushi et al, 2021 , Cai et al, 2021b , Lu et al, 2021 , Reusch et al, 2021 , Wang et al, 2020 ). Similarly, a wide range of metabolic parameters and biomarkers of damage, inflammatory responses, and coagulation system activation have been associated with COVID-19 poor outcomes ( Charoenngam et al, 2021 , Heer et al, 2021 , Khamis et al, 2021 , Kitakata et al, 2021 , Lv et al, 2020 , Manocha et al, 2021 , Nurlu et al, 2021 , Tang et al, 2021 )…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several other cell types such as endothelial cells, hepatocytes and monocytes have been reported to be susceptible to SARS-CoV-2 and infection of these cells may contribute to tissue lesions and/or inflammation ( Hoffmann et al, 2020 ; Hikmet et al, 2020 ; Pontelli et al, 2020 ). Increased cytokine levels, including IL-6, IL10, and TNF-α, are positively correlated with disease severity ( Tang et al, 2021 ; Liu et al, 2021 ). Indeed, several lines of evidence suggest that hyperinflammation may be triggered by virus intracellular sensing pathways in cellular targets, and by activation of infiltrated monocytic and polymorphonuclear cells ( Pantazi et al, 2021 ; Melms et al, 2021 ; Ackermann et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… 27 It has also been reported that the serum C1q level of COVID-19 patients has been reduced, which also further suggests that viral infection plays an important role in the classical complement activation pathway. 28 Our results showed that C1q levels were not significantly related to septic shock. However, previous studies have reported that other complement components are related to the occurrence of shock.…”
Section: Discussionmentioning
confidence: 47%